Paediatric Rhegmatogenous Retinal Detachment: Clinical Features and Surgical Outcomes - Şehnaz Özçalışkan; Gülşah Gümüş; Gökhan Demir; Adem Tellioğlu; Özgür Artunay (Galenos Yayinevi, 2021)
Aim:To evaluate the clinical characteristics, predisposing factors and surgical outcomes of rhegmatogenous retinal detachment (RRD) in paediatric patients.Materials and Methods:This retrospective consecutive case series included 79 paediatric patients diagnosed with RRD who were treated by surgical intervention. Demographic data, predisposing factors, the status of macular involvement, presence of proliferative vitreoretinopathy (PVR), the type of initial surgery, and the surgical anatomical and visual outcomes of the patients were recorded.Results:The study included 79 eyes of 79 children with a mean age of 11.63±4.36 years. There were 59 (74.7%) male and 20 (25.3%) female patients in the study group. The mean follow-up period was 18.65±6.04 months. Trauma (45%) was found to be the most common predisposing factor associated with RRD. Other common predisposing factors were myopia (42%), congenital/developmental anomaly (9%), and history of ocular surgery (4%). Macular detachment was present in 56 eyes (70.8%). At the initial examination, the mean VA (VA) was 1.72±1.01 logMAR (n=60). As a primary surgical treatment, 48 eyes (60.7%) had undergone pars plana vitrectomy (PPV), 11 eyes (13.9%) had scleral buckle (SB), and 20 (25.3%) eyes had PPV combined with SB procedures. Reattachment was achieved in 50 (63.2%) eyes after the first surgery. The final mean VA was improved to 1.58±0.87 logMAR, and the anatomical success rate was 74.6%.Conclusion:This study demonstrated that paediatric RRD is commonly associated with trauma and myopia. Successful outcomes were obtained in both groups after RRD surgery. Although associated with poor visual outcomes, careful ophthalmologic assessment and surgical management can preserve visual functions in children with RRD.